2016
DOI: 10.1159/000443206
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal White Matter Integrity in Elderly Patients with Idiopathic Normal-Pressure Hydrocephalus: A Tract-Based Spatial Statistics Study

Abstract: We investigated white matter integrity utilizing diffusion tensor imaging in patients with idiopathic normal-pressure hydrocephalus (INPH) who had a positive response to the cerebrospinal fluid tap test and in age- and gender-matched Alzheimer's disease (AD) patients. We enrolled 28 patients with INPH, 28 patients with AD and 20 healthy controls. Tract-based spatial statistics demonstrated that INPH patients had lower fractional anisotropy (FA) in the anterior corona radiate (bilateral), corpus callosum, super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Studies of directional diffusion parameters such as FA values were found to be elevated in the corticospinal tracts of patients with iNPH (8). The FA values also showed significant differences in the axons of white matter in iNPH patients compared with patients with neurodegenerative diseases and healthy groups in previous studies (25). Our study found that the MD and AD values increased in iNPH patients, which is consistent with the results in the literature that implied an increase in the diffusion of water molecules.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of directional diffusion parameters such as FA values were found to be elevated in the corticospinal tracts of patients with iNPH (8). The FA values also showed significant differences in the axons of white matter in iNPH patients compared with patients with neurodegenerative diseases and healthy groups in previous studies (25). Our study found that the MD and AD values increased in iNPH patients, which is consistent with the results in the literature that implied an increase in the diffusion of water molecules.…”
Section: Discussionsupporting
confidence: 91%
“…Many measures were used as assessments of cognitive function (Mini Mental State Examination (MMSE), 2129,31,32,3537,4345,48,49 trail making test A (TMT-A), 23,32,33,35,36,43,49 DemTect test, 25 , 32 Montreal Cognitive Assessment (MOCA) 54 ; learning and memory (Hopkins Verbal Learning Task-Revised (HVLT-R) 39 ); verbal fluency and executive function (COWAT), 20 , 39 Wechsler Memory Scale III (WMS-WL), 20 Rey complex figure test (RCFT), 20 according to Deckersbach et al. 71 ); conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control and environmental autonomy due to frontal lobe dysfunction (frontal assessment battery (FAB) 22,24,33,36,37,41,45,49 ); grade of dementia (Clinical Dementia Rating Scale (CDR), 29,35,36 , Clinical Dementia Rating Scale Sum of Boxes (CDR-SOB) 29 ); motor impairment and gait (gait velocity, 43 Timed Up and Go (TUG) test, 22,23,30,3538,41,…”
Section: Resultsmentioning
confidence: 99%
“…showed lower FA and higher MD in the anterior corona radiate, CC, superior longitudinal fasciculus, thalamic radiation, external capsule and middle cerebellar peduncle in iNPH patients in comparison with AD. 36 Ades-Aron et al. found that AD and axial kurtosis differ between iNPH and AD in an area close to the superior IC and corona radiate, reporting greater AD and lower axial kurtosis in the iNPH group in comparison with AD with a p < 0.05.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a systematic review reported that T -tau and p -tau may differentiate iNPH from AD and Aβ 42 from HC (Manniche et al, 2019 ). Diffusion tensor imaging as an MRI technique determining diffusion characteristics of white matter (WM) has been performed in most studies of patients with iNPH (Hattingen et al, 2010 ; Kanno et al, 2011 ; Lenfeldt et al, 2011 ; Hattori et al, 2012 ; Kang et al, 2016 ; Kamiya et al, 2017 ; Saito et al, 2020 ). Griffa et al concluded regarding white matter microstructural alteration of the periventricular, frontal, and temporal regions in patients with iNPH (Griffa et al, 2020 ); however, few studies have investigated gray matter structural changes in such patients.…”
Section: Introductionmentioning
confidence: 99%